Implementasi Program Administrasi Pembayaran Berbasis Dekstop (Studi Kasus: Sma Negeri 1 Cikampek) - Surtika Ayumida; Mohammad Syamsul Azis; Zulfirman Gherar Fiano (Jurnal Interkom: Jurnal Publikasi Ilmiah Bidang Teknologi Informasi dan Komunikasi, 2020)
In this era of globalization, the application of administrative data processing has been used by many parties, both agencies, organizations, as well as in educational institutions that will trigger the performance of agencies to be better than before. The payment data processing of SPP on SMA Negeri 1 Cikampek until now are still operating manually, so that activities associated with the administration is still slow even still queued to make payments. Specifically the functions performed by the application payment administration developed include, student data collection, alumni data, SPP Payment, and collection payment. Display student information, alumni information, payment SPP reports, until collection reports. This application payment administration is developed using Java programming language. With this computerized payment sistem hopely to improve the data processing of SPP payment, bimbingan study, study tour, and others effectively and efficiently.